Man on fire [videorecording (DVD)] - Washington, Denzel, 1954-; Fanning, Dakota, 1994-; Walken, Christopher, 1943-; Quinnell, A. J. (Denzel Washington collection., 2004)
"Hard-drinking, burnt-out CIA operative John Creasy (Washington) has given up on life -- until his friend Rayburn ... gets him a job as bodyguard to nine-year-old Pita Ramos ... Bit by bit, Creasy begins to reclaim his soul, but when Pita is kidnapped, Creasy's fiery rage is released and he will stop at nothing to save her"--Container.